IDH1/2 wildtype gliomas grade 2 and 3 with molecular glioblastoma-like profile have a distinct course of epilepsy compared to IDH1/2 wildtype glioblastomas. Issue 4 (16th August 2022) - van Opijnen, Mark P; Tesileanu, C Mircea S; Dirven, Linda; van der Meer, Pim B; Wijnenga, Maarten M J; Vincent, Arnaud J P E; Broekman, Marike L D; Dubbink, Hendrikus J; Kros, Johan M; van Duinen, Sjoerd G; Smits, Marion; French, Pim J; et al.
Abstract: Background: IDH1/2 wildtype (IDHwt) glioma WHO grade 2 and 3 patients with p TERT mutation and/or EGFR amplification and/or + 7/−10 chromosome gain/loss have a similar overall survival time as IDHwt glioblastoma patients, and are both considered glioblastoma IDHwt according to the WHO 2021 classification. However, differences in seizure onset have been observed. This study aimed to compare the course of epilepsy in the 2 glioblastoma subtypes. Methods: We analyzed epilepsy data of an existing cohort including IDHwt histologically lower-grade glioma WHO grade 2 and 3 with molecular glioblastoma-like profile (IDHwt hLGG) and IDHwt glioblastoma patients. Primary outcome was the incidence proportion of epilepsy during the disease course. Secondary outcomes included, among others, onset of epilepsy, number of seizure days, and antiepileptic drug (AED) polytherapy. Results: Out of 254 patients, 78% (50/64) IDHwt hLGG and 68% (129/190) IDHwt glioblastoma patients developed epilepsy during the disease ( P  = .121). Epilepsy onset before histopathological diagnosis occurred more frequently in IDHwt hLGG compared to IDHwt glioblastoma patients (90% vs 60%, P  < .001), with a significantly longer median time to diagnosis (3.5 vs 1.3 months, P  < .001). Median total seizure days was also longer for IDHwt hLGG patients (7.0 vs 3.0, P  = .005), and they received more often AED polytherapy (32% vs 17%, P  = .028). Conclusions: Although the incidence proportion of epilepsy during the entire disease course is similar, IDHwt hLGG patients show a significantly higher incidence of epilepsy before diagnosis and a significantly longer median time between first seizure and diagnosis compared to IDHwt glioblastoma patients, indicating a distinct clinical course.